TECHNOLOGY FOR HIDING INFORMATIVE CONTENT IN THE DYNAMIC STREAM OF VIDEO SEGMENTS. - Barannik, Dmytro (Science-based technologies, 2024)
The article shows that in the conditions of wartime, information confrontation, it is important to provide timely reliable information with limited time of relevance. Examples of such situations are the organization of "live" access to remote information in real time using unmanned platforms at a considerable distance from decision-making centres. The existence of cases of imbalance between the requirements for ensuring the required level of information security categories and limited capabilities for the performance of remote infocommunication systems is substantiated. The consequences are: loss of availability and integrity of video resources; limited ability to ensure the required level of confidentiality in the face of strict requirements for the organization of the availability of video information. Thus, the article proves that it is important to ensure the necessary level of information security of video information resources using infocommunication technologies based on unmanned platforms. It is shown that the existing concepts of implementation of issues of information security of video data for on-board complexes are based on the concept of a sequential scheme. At the same time, this concept has certain disadvantages. As an alternative approach, the article proposes to additionally use steganographic conversion technologies in combination with cryptographic protection methods. In this case, it becomes possible to hide the most significant informative resources in the general video information flow. At the same time, it is argued that the existing technologies of steganographic transformations have certain shortcomings, which are manifested in the contradiction between the groups of basic indicators of the quality of information embedding. The creation of a rule for hiding informative content in the process of structural steganocompression coding is outlined. For the first time, structural steganocompression coding was developed based on the implantation of a bit of concealed content in the second position in the quilted sequence with a modified basis. A distinctive feature of the method is that without introducing distortions into the stegano-codogram, it is ensured that the signs of the presence of a number of steganographic structural redundancy are eliminated. Steganographic decoding based on the simultaneous restoration of elements of the video sequence and the element of hidden content embedded in its second position has been developed.